The influence of no-core fibre length on the sensitivity Optical fibre Humidity sensor - Kashen, Suroor Lazem; Taher, Hanan J. (Iraqi Journal of Laser, 2021)
Abstract: Reflection optical fibre Humidity sensor is presented in this work, which is based on no core fibre prepared by splicing a segment of no core fibre (NCF) at different lengths 1-6 cm with fixed diameter 125 µm and a single mode fibre (SMF). The range of humidity inside the chamber is controlled from 30% to 90% RH at temperature 30 °С. The experimental result shows that the resonant wavelength dip shift decreases linearly with an increment of RH% and the sensitivity of the sensor increased linearly with an increasing in the length of NCF. However, a high sensitivity 716.07pm/RH% is obtained at length 5cm with good stability and reputability. Furthermore, the sensor is shifted towered a short wavelength (Blue shift).